Cognitively central actors and their personal networks in an energy efficiency training program - Hytönen, Kaisa; Palonen, Tuire; Hakkarainen, Kai (Frontline Learning Research, 2014)
This article aims to examine cognitively central actors and their personal networks in the emerging field of energy efficiency. Cognitively central actors are frequently sought for professional advice by other actors and, therefore, they are positioned in the middle of a social network. They often are important knowledge resources, especially in emerging fields where standard knowledge exchange mechanisms are weak. By adopting a personal network approach, we identified the cognitively central participants of a one-year energy efficiency training program, studied the structure and heterogeneity of their personal networks and determined which features were relevant to achieving these cognitively central positions. At the end of the training, the social networking questionnaire was sent to 74 course participants. Semi-structured interviews were conducted for the six most-central actors, whose personal networks were larger than those of the other participants. These six actors differed from each other in many respects; there did not appear to be a single explanation for why these persons achieved their central positions. In conclusion, we propose that becoming a cognitively central actor is an intricate process. It cannot be explained only, for instance, by actors’ educational backgrounds, the level of their previous energy efficiency knowledge or their field of know-how. To understand this phenomenon, we must examine which organizations such people come from and how their expert profiles, which are related to their fields and competences, fit into the wider context of energy efficiency. More research is needed to determine whether the results are only typical of emerging fields.